Cortico-Hippocampal Oscillations Are Associated With the Developmental Onset of Hippocampal-Dependent Memory - García-Pérez, María A.; Irani, Martin; Tiznado, Vicente; Bustamante, Tamara; Inostroza, Marion; Maldonado, Pedro E.; Valdés, José L. (Frontiers in Neuroscience, 2022)
Hippocampal-dependent memories emerge late during postnatal development, aligning with hippocampal maturation. During sleep, the two-stage memory formation model states that through the hippocampal-neocortical interactions, cortical slow-oscillations (SO), thalamocortical Spindles, and hippocampal sharp-wave ripples (SWR) are synchronized, allowing the consolidation of hippocampal-dependent memories. However, evidence supporting this hypothesis during the first weeks of development is still lacking. Therefore, we performed successive object-in-place tests during the temporal window of memory emergence and recorded in-vivo, the occurrence of SO, Spindles, and SWR during sleep, immediately after the memory encoding stage of the task. We found that hippocampal-dependent memory appears at P32 independently of task overtraining. Furthermore, we observed that those animals with better performance in the memory task had increased Spindle density and duration and lower density of SWR. Moreover, we observed changes in the SO-Spindle and Spindle-SWR temporal-coupling during the 3-6 postnatal weeks. Our results provide new evidence regarding hippocampal-dependent memory onset and its relationship with the oscillatory phenomenon that helps us understand how adult memory consolidation models fit in the early stages of postnatal development.